Review the Success of the Mobile Government from the Government Perspective - Noor Dheyaa Azeez; Muhammad Modi Lakulu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
The researchers agreed on the potential of the mobile government as a new channel of communication between the government and citizens if the mobile government eliminates the traditional organizational structure of government, thus changing the way information is exchanged between them, and provide government services in a transparent manner at anytime and anywhere. For the education sector, mobile education initiatives must be successful in educational institutions must choose the appropriate technology in proportion to its infrastructure to conserve resources and reduce the stress of change. Therefore, this research seeks to present the most important factors of success explored by researchers in their studies, using different research methods in different countries, and trying to classify these factors from the perspective of the government and citizens. The methodology used in this research is to review the literature on the success of mobile government from a government perspective, in order to determine the success factors adopted by each study, and then categorize the success factors according to the degree of their impact on the successful implementation of the mobile government. The final stage is a model proposal for mobile government success.